Proceedings of the 2nd International Seminar on Education Research and Social Science (ISERSS 2019) 2019
DOI: 10.2991/iserss-19.2019.263
|View full text |Cite
|
Sign up to set email alerts
|

On Museum Tourism Development from the Perspective of Cultural Identity Experience — Taking the Core Area of the 21st Century Maritime Silk Road as an Example

Abstract: Cultural identity experience involves a process of self-identification, which helps to strengthen cultural confidence. As the core area of the 21st Century Maritime Silk Road, Fujian Province represents an important starting point and birthplace of the ancient Maritime Silk Road, while numerous museums are the symbols of the culture in the region. At present, the tourism development of China's Marine Silk Museum faces five constraints: static display restricts comprehensive perception, emotional barriers restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…When a person is highly identified with a culture or even becomes an integral part of his or her own culture, he or she is bound to be loyal to that culture because it is already an important part of his or her culture, psyche and spirit. Therefore, the influence of cultural identity on cultural confidence (Luo et al, 2019;Gao, 2021) and the influence of cultural identity on cultural loyalty (Tian et al, 2020;Lee et al, 2021) in this study are reasonable and in line with previous research.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When a person is highly identified with a culture or even becomes an integral part of his or her own culture, he or she is bound to be loyal to that culture because it is already an important part of his or her culture, psyche and spirit. Therefore, the influence of cultural identity on cultural confidence (Luo et al, 2019;Gao, 2021) and the influence of cultural identity on cultural loyalty (Tian et al, 2020;Lee et al, 2021) in this study are reasonable and in line with previous research.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 90%
“…From the perspective of tourism, tourism contributes to the spread of culture, facilitates communication and brings in funds for the preservation of culture, and in this sense, tourism contributes to the cultural identity of tourists. Luo et al (2019) conducted a study with tourists visiting the 21st Century Maritime Silk Road Museum and found that visitors who experienced the museum had a high cultural identity, and a strong study by Gao (2021) found that enhancing students' national cultural identity helped build students' national cultural self-confidence. Tian et al (2020) conducted a study on tourists who participated in intangible cultural heritage experiences and found that tourists' cultural identity would influence cultural destination loyalty through authenticity.…”
Section: Cultural Identitymentioning
confidence: 99%
“…A clear example of this is its application within culture. Just like Augmented Reality, museums are experiencing a considerable boom thanks to their broad tourist appeal, resulting in a considerable increase in ever more diverse visitors (Choi et al, 2020;Luo et al, 2019;Shalina, 2015). This human and economic influx has also necessitated considerable reinvention in recent decades.…”
Section: Introductionmentioning
confidence: 99%